Great negotiators : How the most successful business negotiators think and behave. - Beasor, Tom, 1951- (VT : Gower, 2006)
What is it about the great negotiators? How is it they seem to manage to recover from disadvantageous positions? How do they adapt their approach to turn an unpromising start into a value creating deal? And why is it that they never seem to lose their app.